Assessing Polytechnic Students’ Dependency on AI Tools in ESP Writing - Nouval, Alvin; Kartikasari, Prima Beauty (Transpublika Publisher, 2025)
The rapid integration of Artificial Intelligence (AI) tools in language education has reshaped writing practices, particularly in English for Specific Purposes (ESP) contexts. This study investigates Polytechnic students’ dependency on AI tools in Business English writing, focusing on how AI use influences writing self-efficacy and perceived autonomy. A qualitative research design was employed involving 25 undergraduate students enrolled in a Business English course. Data were collected through open-ended questionnaires and analyzed using thematic analysis to identify recurring patterns related to AI use, confidence, dependency, and feedback perceptions. The findings reveal that students primarily perceive AI as a language enhancement tool that improves vocabulary, grammar, translation accuracy, and writing efficiency. However, strong functional dependency emerged, particularly at the lexical and sentence levels, with several students reporting reduced confidence when writing without AI assistance. While AI-generated feedback was valued for clarity and immediacy, human feedback from lecturers and peers was considered more contextually meaningful and pedagogically authoritative. Students also expressed awareness of risks such as overreliance, reduced effort, and ethical concerns. The study concludes that AI serves as both a supportive scaffold and a potential source of dependency. Effective and structured pedagogical integration is essential to ensure that AI enhances rather than replaces students’ independent writing competence.